2016
DOI: 10.1111/ejn.13368
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine‐sensitive intracellular Ca2+ channels are involved in the output from the SCN circadian clock

Abstract: The suprachiasmatic nuclei (SCN) contain the major circadian clock responsible for generation of circadian rhythms in mammals. The time measured by the molecular circadian clock must eventually be translated into a neuronal firing rate pattern to transmit a meaningful signal to other tissues and organs in the animal. Previous observations suggest that circadian modulation of ryanodine receptors (RyR) is a key element of the output pathway from the molecular circadian clock. To directly test this hypothesis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Interestingly, pharmacological disruption of RyR function abolishes circadian rhythms in [Ca 2+ ] i level, electrical activity and behaviour (Ikeda et al., ; Mercado et al., ), suggesting that this is a key link between the molecular and electrical oscillations in SCN neurons. Indeed, members of the molecular clock, Bmal1 and Cry1 , interact to modulate the activity of the RyR2 transcription (Pfeffer et al., ; Ikeda & Ikeda, ), while pharmacological activation of the RyRs causes excitation in SCN neurons (Aguilar‐Roblero et al., , ). Together, this suggests that clock‐operated intracellular calcium store release contributes to the up‐state of SCN neurons during the day.…”
Section: Intra‐ and Intercellular Signallingmentioning
confidence: 99%
“…Interestingly, pharmacological disruption of RyR function abolishes circadian rhythms in [Ca 2+ ] i level, electrical activity and behaviour (Ikeda et al., ; Mercado et al., ), suggesting that this is a key link between the molecular and electrical oscillations in SCN neurons. Indeed, members of the molecular clock, Bmal1 and Cry1 , interact to modulate the activity of the RyR2 transcription (Pfeffer et al., ; Ikeda & Ikeda, ), while pharmacological activation of the RyRs causes excitation in SCN neurons (Aguilar‐Roblero et al., , ). Together, this suggests that clock‐operated intracellular calcium store release contributes to the up‐state of SCN neurons during the day.…”
Section: Intra‐ and Intercellular Signallingmentioning
confidence: 99%
“…) and the night (Aguilar‐Roblero et al . ). Consistent with this, in some SCN neurons RyR inhibition caused a significant increase in firing rate during the night, via loss of activation of the BK Ca 2+ ‐activated K + current (Whitt et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Aguilar‐Roblero et al . , ). However, the effects of RyR inhibitors on firing frequency can be heterogeneous between individual neurons (Diaz‐Munoz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that ER Ca 2+ release activated plasma membrane K + channels and contributed to the after hyperpolarizing potentials (AHPs), which then reduced neuronal activity in otic ganglion cells (Yoshizaki et al, 1995). Blocking RyRs/Ca 2+ -release channels with high doses of RY (100 μM) suppressed the rhythm in [Ca 2+ ] i and partially reduced the amplitude of the rhythm in the spike frequency of suprachiasmatic nucleus neurons in acute rat slices (Aguilar-Roblero et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…RyRs activation by caffeine and RY has been shown to induce apoptosis in hamster ovary cells via the depletion of intracellular Ca 2+ (Pan et al, 2000), but RyRs inhibition for 24 h did not induce death in MIN6 cells (Luciani et al, 2009). Inhibiting IP 3 Rs, which disturbs constitutive Ca 2+ transfer to the mitochondria, influences ATP production and leads to the activation of AMP-activated kinase (AMPK) and a subsequent increase in basal autophagic flux as a compensatory pro-survival response (Aguilar-Roblero et al, 2016). However, chronic IP 3 Rs inhibition with 2-aminoethoxydiphenyl borate and Xes decreased the survival of DA neurons in midbrain cultures (Missiaen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%